ANTIOXIDANT AND ANTICANCER STUDIES OF CHLOROFORM EXTRACT OF MORINDA PUBESCENS LEAF - jaya kumar; Arockia samy; Archana sri; Dr.(Sr.)Jaya Santhi (International Journal of Phytomedicine, 2013)
Morinda pubescens is used for the treatment of diabetes, liver diseases, wound healing, cancer etc and this study was aimed to screen the chloroform extract of Morinda pubescens leaves for biologically active compounds and to evaluate the antioxidant and anticancer potential against HepG2 cell lines. The antioxidant activity of extract and its isolated compounds were carried out using 2, 2 diphenyl-1-picrylhydrazyl assay using L- ascorbic acid as a standard. The tetrazolium salt 3-[4, 5 dimethylthiazol-2yl]-2,5diphenyl trazolium bromide was used to determine the cell viability against HepG2 cells and Caspase-3 and -9 carried out to find the mechanism of the cytotoxicity. Octonyl glucopyranose, the isolated bioactive compound was subjected to RT-PCR study to confirm the apoptotic activity. The results revealed that the chloroform extract and three isolated compounds namely phytol, Octonyl glucopyranose and hexonyl glucopyranose exhibited significant antioxidant activities with IC50 values of 550, 758, 482 and 645μg/mL respectively. The Octonyl glucopyranose one of the isolated bioactive compounds decreased the cell viability in HepG2 cells dose-dependently and increased the caspase-3 and caspase-9 protein levels to 1.3 folds than the normal cells. Augmentation of p53 expression was observed in the Octonyl glucopyranose treated cells than the untreated cells. These findings might offer valuable insights into the mechanism of anti-cancer activity of Octonyl glucopyranose HepG2 cells.